Core Symptoms and Symptom Relationships of Problematic Internet Use in Children and Adolescents: A Network Analysis. - Li, Qi; Zhou, Hui; Meng, Guangteng; Xiao, Jing; Hu, Kesong; Wei, Ping; Wang, Jinpeng; Du, Mei; Liu, Xun (International Journal of Mental Health & Addiction, 2026)
With the advancement of Internet technology, problematic Internet use (PIU) has become one of the most common mental health issues among children and adolescents. This study employed network analysis to identify the central symptoms and network connections of PIU, as well as the differences in these complex patterns between children and adolescents. For this purpose, the study included 10,530 participants aged 8–18 years, with participants aged 8–12 classified as the child group and those aged 13–18 classified as the adolescent group. All participants completed the Internet Addiction Test (IAT). The results of the network analysis for the overall sample of children and adolescents indicated that "Anticipate going online again" and "Neglect chores for online time" were the core nodes in the network for both groups. Moreover, the network structure differed between children and adolescents. Compared to children, the adolescent network showed increased relationships between "Prefer internet excitement to close friends" and "Prefer online time over socializing," "Reluctant to log off ("just a little longer")," and "Fail to cut down online time." This study provided empirical support for more effective and timely interventions and treatments tailored to different age groups by identifying the core symptoms and complex relationships of PIU in the symptom networks of children and adolescents.